Towards Malaria Elimination A Leap Forward - Manguin, Sylvie; Dev, Vas (IntechOpen, 2018)
Towards Malaria Elimination - A Leap Forward was started to mark the occasion for renewed commitment to end malaria transmission for good (the WHO's call for "Malaria Free World" by 2030). This book is dedicated for the benefit of researchers, scientists, program and policy managers, students and anyone interested in malaria and other mosquito-borne diseases with the goal of sharing recent information on success stories, innovative control approaches and challenges in different regions of the world. Some main issues that emerged included multidrug-resistant malaria and pandemic risk, vaccines, cross-border malaria, asymptomatic parasite reservoir, the threat of Plasmodium vivax and Plasmodium knowlesi, insecticide resistance in Anopheles vectors and outdoor malaria transmission. This book is one little step forward to bring together in 17 chapters the experiences of malaria-expert researchers from five continents to present updated information on disease epidemiology and control at the national/regional level, highlighting the constraints, challenges, accomplishments and prospects of malaria elimination.